2023
DOI: 10.3390/ijms24076051
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Biomarkers in Manifest and Premanifest Huntington’s Disease

Abstract: Huntington’s disease (HD) is characterized by clinical motor impairment (e.g., involuntary movements, poor coordination, parkinsonism), cognitive deficits, and psychiatric symptoms. An inhered expansion of the CAG triplet in the huntingtin gene causing a pathogenic gain-of-function of the mutant huntingtin (mHTT) protein has been identified. In this review, we focus on known biomarkers (e.g., mHTT, neurofilament light chains) and on new biofluid biomarkers that can be quantified in plasma or peripheral blood m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 97 publications
0
8
0
Order By: Relevance
“…In recent years, emerging studies suggest that mechanisms underlying many neurodegenerative diseases extend beyond the brain [ 57 , 58 , 59 , 60 , 61 ]. This includes phenomena such as protein aggregation and mitochondrial dysfunction in peripheral organs, alterations in peripheral metabolism, and peripheral inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, emerging studies suggest that mechanisms underlying many neurodegenerative diseases extend beyond the brain [ 57 , 58 , 59 , 60 , 61 ]. This includes phenomena such as protein aggregation and mitochondrial dysfunction in peripheral organs, alterations in peripheral metabolism, and peripheral inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to mHTT, several potential biomarkers have been evaluated, such as S100 calcium-binding protein B (S100B), NfL, and tau protein. However, many of these molecules have not shown significant differences between HD patients and healthy controls and did not correlate with disease severity [110,111].…”
Section: Huntington's Diseasementioning
confidence: 99%
“…Longitudinal study of such individuals has identified a number of early symptoms, including autonomic symptoms [ 30 ] and neuropsychiatric symptoms including depression, apathy, irritability and altered executive function [ 31 , 32 ]. Early investigation into biomarkers in HD suggests a promising role for serum neurofilament light protein; this has been shown to correlate with clinical and radiological changes in HD [ 33 ].…”
Section: Lessons From Other Diseasesmentioning
confidence: 99%